Drug Induced Long QT - Januar Wibawa Martha (Jurnal Kardiologi Indonesia, 2008)
A 54 years old cattle-farm owner was found un-conscious by his daughter at his living room. After she repeatedly shook his body, he regained consciousness without any impairment. He told his daughter that before collapse he suddenly felt weakness all over his body, a bit lightheaded and a brief period of palpitation. On the next day he experienced the same symptom, and this time he fainted at the farm. He was rushed to 24-hour infirmary, but he recovered before reaching the clinic. He afterwards was seen by a doctor and was told to have a mild stroke. He was referred to emergency department at a nearby hospital where he passed out for the third time; but this time was witnessed by his daughter. She noted that before he fell down, he was having a short period of seizure. A neurologist was among the first physician who saw him and noticed that the patient had a very slow pulse. He accordingly consulted the patient to cardiologist due to bradycardia.